A Tale Twice Told: Between Variants and Versions in the Transmission of Mandaic Spells - Morgenstern, Matthew (Maarav, 2024)
In contrast to Mandaic magic spells that have survived in epigraphic sources dating from the fifth to seventh centuries which show considerable literary variation, those attested in manuscript sources—the earliest surviving example of which was copied in the seventeenth century—mostly preserve only a single recension of each spell. One rare exception is a spell that has been incorporated in a longer and shorter recension into two different collections of formulae, Šap̄ta ḏ-Pašar Haršia "The Scroll of the Exorcism of Sorceries" and Šap̄ta ḏ-Mihla ḏ-Sidma ḏ-Sahria u-Kibša ḏ-Daiuia (Pašar Mihla) "The Scroll of Salt, the Restraint of Sahirs and the Subduing of Devs (The Exorcism of Salt)." This article presents an editio princeps of both recensions of this spell with a translation and brief philological notes and emphasizes the importance of examining all available textual witnesses and establishing the relationship between them when such an edition is produced. It is shown that where the two traditions of transmission of this spell are parallel, some of the textual variants appear to reflect slightly different versions of the text that were incorporated into the two collections, while others have probably arisen at a later stage in the transmission of each collection.